Comparison of the bleached and non-bleached teeth for the adhesive boosters for the orthodontic bonding: An original research - V Arun Deepak; Ekavenika Kovelakar; Prince K Chacko; Pradeep Kandikatla; Lalima Kumari; Praveen K Varma (Wolters Kluwer Medknow Publications, 2023)
Introduction: The bleaching of the teeth is known to reduce the bonding of the orthodontic brackets. Hence, this in vitro study was piloted to analyze if there was any variance between the teeth that were and were not bleached when the adhesive boosters were used and for its effect on the shear bond strength. Materials and Procedures: Hundred premolars (maxillary) that had been excised were randomly split into two groups: bleached teeth and unbleached teeth. The bleaching agent was gel composed of 22% carbamide peroxide. Maxillary premolar brackets were bonded, and each group was subdivided as control and adhesive booster Enhance LC groups. A universal testing device was used for debonding. The SBS thus recorded was compared for the subgroups and groups. Results: Significant variance was obtained for between the groups and between the subgroups. Higher bond strength was for the non-bleached teeth than the bleached teeth and was seen in the adhesive booster subgroup than the control group. Conclusion: In summary, adhesive boosters dramatically raised the shear bond strength of teeth irrespective of the bleaching. Further in vivo studies are suggested.